Optimization of cellulase-free xylanase production by thermophilic streptomyces thermovulgaris TISTR1948 through Plackett-Burman and response surface methodological approaches - Chaiyaso T. (2014)
Cellulase-free xylanase production by thermophilic Streptomyces thermovulgaris TISTR1948 was cultivated in a basal medium with rice straw as sole source of carbon and as an inducible substrate. Variable medium components were selected in accordance with the Plackett-Burman experimental design. The optimization conditions of physical factors (pH and temperature levels) were then combined in further studies through the response surface methodology approach. Only two significant components, rice straw and yeast extract, were chosen for the optimization studies. A secondorder quadratic model was constructed by central composite design (CCD). The model revealed that both pH and temperature levels were significant, and were dependent on xylanase production. Under these experimental designs, the xylanase yield increased from 51.11 to 274.49 U/mL (3,400 to 10,000 U/g of rice straw) or about 537% higher than an unoptimized basal medium. The optimum conditions to achieve maximum yield of xylanase were 27.45 g/L of rice straw and 5.42 g/L of yeast extract under relatively neutral conditions of pH 7.11, 50.03 °C, and a incubation period.